Pengaruh Pemberian Jus Semangka terhadap Kelelahan Otot dan Delayed Onset Muscle Soreness setelah Latihan Beban (The effect of Watermelon Juice on Muscle Fatigue and Delayed Onset Muscle Soreness after Weight Training) - Prayoga Adinawer Sirait; Cholis Abrori; Enny Suswati (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
The main problem that is often faced by athlete is fatigue. It can decrease maximum muscle strength. To overcome this problem, many athletes use ergogenic aids such as watermelon. The purpose of this study was to determine the effect of watermelon juice on reduction of muscle fatigue and delayed onset muscle soreness (DOMS) after weight training. Muscle fatigue was measured by maximum repetition done by the subjects in the last set and DOMS was measured by post-training muscle soreness intensity. By using a randomized crossover design, 20 subjects were recruited then divided into 2 groups, a treatment group and a control group. The subjects were asked to do a training protocol to induce muscle fatigue and DOMS. As much as 500 ml watermelon juice was consumed in 1 of 2 training sessions and a placebo was consumed in the other. The number of repetitions showed a significant increase on treatment group than control group (p<0,05). Passive muscle soreness intensity and active muscle soreness intensity showed a significant decrease on 24 hours and 48 hours post-training after administration of watermelon juice (p=0,000). We conclude that there was an effect of watermelon juice on muscle fatigue and DOMS after weight training. Keywords: weight training, muscle fatigue, DOMS, watermelon, citrulline